Photovoltaic Waste Assessment and Recovery Potential: A Case Study in Chile - Ozturk, Samet (Mdpi, 2025)
Recently, there has been a surge in the popularity of renewable energy systems due to their lucrative and sustainable attributes. Among these, photovoltaic (PV) systems stand out as prominent examples. Nevertheless, it is imperative to ascertain the management of waste produced by these systems in order to mitigate environmental pollution and harness their economic potential. This study aims to assess the present status and forecast the accumulation of waste generated by PV power plants in Chile. Utilizing openly available public data, a database is constructed to track the accumulation of waste. Two scenarios, namely, early-loss and regular-loss scenarios are employed to estimate the projected accumulation of PV waste. The findings indicate that by the years 2035 and 2043, the accumulation of waste is estimated to reach 100,000 tons under the early-loss scenario and regular-loss scenario. The total anticipated waste from solar PV modules is projected to be 284,906 tons, with c-Si PV modules contributing 175,595 tons to this total in Chile. Remarkably, it is determined that more than 235,000 tons of materials from this waste is recoverable, amounting to nearly USD 781 million in economic value. Silver is projected to bring the most economic value, with nearly USD 379 million, while lead, tin, cadmium, and zinc are each valued at less than USD 1 million. This study highlights the importance of promoting the sustainable development of PV systems, particularly in alignment with Sustainable Development Goals 7 (Affordable and Clean Energy) and 13 (Climate Action). Future research is expected to place greater emphasis on eco-design approaches in PV module production.
Keywords: photovoltaic modules; waste; recycling; Chile; sustainable development